Regulators of endothelial and epithelial barrier integrity and function in acute lung injury - Lucas, Rudolf (Biochem Pharmacol, 2009)
Permeability edema is a life-threatening complication accompanying acute lung injury (ALI), severe pneumonia and the acute respiratory distress syndrome (ARDS), which can be associated with a reduced alveolar liquid clearance (ALC) capacity, a disruption of the alveolar epithelial barrier, and an increased capillary endothelial permeability. Bacterial and viral infections can directly promote pulmonary endothelial hyperpermeability and indirectly decrease the function and/or expression of ion transporters regulating ALC in type II alveolar epithelial cells, by means of inducing a strong inflammatory and oxidative stress response in the infected lungs. Apart from ventilation strategies, no standard treatment exists for permeability edema, making the search for novel regulators of endothelial and epithelial hyperpermeability and dysfunction important. Here, we present an overview of recently identified substances that inhibit and/or reverse endothelial barrier disruption and permeability or alveolar epithelial dysfunction: 1) zinc chelators, which were shown to attenuate the effects of oxidative stress on the pulmonary endothelium; 2) peroxisome proliferator activated receptor (PPAR) ligands, which have been shown to exert antiinflammatory effects, by decreasing the expression of pro-inflammatory genes; 3) extracellular ATP, produced during inflammation, which induces a rapid and dose-dependent increase in transendothelial electrical resistance (TER) across pulmonary endothelial cells; 4) the lectin-like domain of TNF, which is spatially distinct from the receptor binding sites and which protects from hydrostatic and permeability edema and 5) Hsp90 inhibitors, which prevent and repair toxin-induced hyperpermeability. Unraveling the mechanism of action of these agents could contribute to the development of novel therapeutic strategies to combat permeability edema.